Coping with resource crises crises. Peoples' struggle for sustainable livelihoods in Pearl Lagoon, Nicaragua / Camilla Andreassen - Andreassen, Camilla (2004)
In this analysis I have identified different coping strategies employed in Haulover, Kakabila and Orinoco, three communities in Pearl Lagoon, Nicaragua. Furthermore, I have determined what influences people's ability to implement successful coping strategies and the importance of social networks; deterioration of natural resources causes crises regardless of where it strikes. The crises, however, are of much greater extent and more crucial character in areas where the natural resources are the only means of survival. The problem statement is how crises caused by resource deterioration are handled locally in a developing country, like Nicaragua, where people are living on the edge of subsistence. While the problem statement is of a general character, the research questions are more specific providing the limits for the research; the theories of sustainable livelihoods and copmg strategies m general, and the theories of intensification, migration, livelihoods diversification and social capital in particular, make up the theoretical framework for this thesis and form the basis for the analysis. Keywords are: vulnerability and security, networking, access to capitals, natural resources and sustainable utilization of such; qualitative methods such as unstructured, intense interviews, conversations, group discussion and observations have been used for collecting primary data during five months of field work in Pearl Lagoon, Nicaragua. The sampling of population was started out by using contact persons in each community and carried on by using the 'snow ball' method. The presentation of primary data is solely of qualitative character using quotations and observations as evidence; The evidence shows that people in poor, rural communities m Pearl Lagoon, Nicaragua intensify, migrate and diversify in order to maintain sustainable livelihoods. The amount of social capital varies between the communities and it seems like presence of financial! capital affects the relations between people. Furthermore, evidence shows that the possibilities and opportunities for poor people to change their situation in poor communities are not only determined by their own struggle against poverty and their ability to implement successful coping strategies, but also by extremal factors like access to a sustainable natural resource base, regulations conceding management of resources and presence/absence of officially appointed controlling bodies. Many seem to be caught in a poverty trap, however, which resource management alone is not able to bring them out of. Extremal factors like economic and welfare policies beyond the fisheries are also needed